Adsorption Capacity And Kinetics Study Of Aqueous Ethanol Purification Using Nigerian Woods Sawdust - Taiwo, E.A.; Iragunima, S.I. (Ife Journal of Technology, 2010)
Bio-ethanol offers advantages of clean burning and reduced engine emission. However, its bioconversion technology is not cost- and energy-effective especially its purification pass the azeotropic point, hence the need for improving on the separation technology of its production. Adsorption by zeolites has been put forward as a means of concentrating the bio-ethanol above 95.5% w/w ethanol. This study investigates the capacity of some Nigerian woods sawdust as adsorbent for aqueous ethanol purification by liquid phase equilibrium adsorption process. To enhance adsorption capacity, the samples were modified using NaOH and H2SO4. Also, pseudo first- and second- order kinetics of the sorption process were studied. Out of the samples experimented; Cordia millenii, Milicea excelsia and Masilania accuminata demonstrated high capacity for water removal with percentage removal of 82, 80 and 75 percent, respectively. Upon acid modification, the capacity improved greatly. The adsorption process followed pseudo second order kinetics with particle-diffusion controlling the transport process. Modification with H2SO4 enhances the performance of the adsorbent.